Metformin use is associated with a lower risk of osteoporosis in adult women independent of type 2 diabetes mellitus and obesity. REDLINC IX study. (3rd May 2020) - Blümel, Juan E.; Arteaga, Eugenio; Aedo, Sócrates; Arriola-Montenegro, José; López, Marcela; Martino, Mabel; Miranda, Carlos; Miranda, Octavio; Mostajo, Desireé; Ñañez, Mónica; Ojeda, Eliana; Pilnik, Susana; et al.
Abstract: Metformin may decrease cell senescence, including bone; hence we aimed at evaluating the association between metformin use and osteoporosis. This was a cross-sectional study carried out in 1259 Latin American adult women aged 40 or more who were not on anti-osteoporotic drugs, were on metformin and had a bone densitometry performed. Of the whole sample, 40.3% reported being on metformin (at least 1 year), 30.2% had type 2 diabetes mellitus and 22.6% had osteoporosis. Median (interquartile range) body mass index (BMI) for the whole cohort was 27.7 (4.6) kg/m 2 and 30.2% had type 2 diabetes mellitus. Current use of hormone therapy, calcium, and vitamin D corresponded respectively to 10.7%, 47.7%, and 43.1% of all surveyed women. A logistic regression model was used to analyze the association of osteoporosis with various covariates incorporated into the model such as age (OR: 1.07, 95% CI: 1.05–1.09), BMI (OR: 0.92, 95% CI: 0.89–0.96) and metformin use (OR: 0.44, 95% CI: 0.32–0.59). Metformin use, regardless of the presence of type 2 diabetes or obesity, was associated with a lower risk of osteoporosis in adult women. We propose that one explanation for this observation could be the effect of the drug over cellular senescence.